Technological Innovation in Learning the Quran through Android Applications in Ummi Method Learning Management on the Ghoroibul Qur'an Material - Muhammad Ryan Maulana; Jarkawi Jarkawi; Husnul Madihah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The use of application-based digital media provides a solution to the problem of limited teacher and student access to Ghoroibul Qur'an text and audio materials that have been distributed unstructured through WhatsApp and YouTube. This application is designed to be accessible offline and integrated with the Ummi curriculum, thereby increasing learning efficiency, student independence, and assisting teachers in the planning, implementation, and evaluation of learning. This study aims to identify teacher and student obstacles in the learning process and recommend an innovative model of Android application-based learning media as an alternative solution. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the developed application acts as an innovative media that combines text and audio materials in one platform, can be accessed without an internet connection, and is designed to meet field needs. This recommendation is considered innovative in supporting more efficient, standardized, and relevant learning management to the development of technology-based Islamic education in the digital era.